The Role Of Leadership And Collaboration In Enhancing The Digital Skills Of Young Entrepreneurs In The Era Of The Covid-19 Pandemic - Fachrurazi, Fachrurazi (BADAN PENERBIT STIEPARI PRESS, 2023)
The Covid-19 pandemic has upended global order by hastening digital transformation, forcing many entrepreneurs to undergo significant changes. The purpose of this research is to determine the impact of digital leadership and collaboration on the digital skills of young entrepreneurs in the Covid-19 pandemic era. Non-probability sampling was used in the empirical analysis, which yielded 147 millennial entrepreneurs. The data were analyzed using multiple linear regression analysis techniques after passing the reliability and validity tests. According to the findings, digital collaboration has a significant impact on the skills of young entrepreneurs. Meanwhile, digital leadership has no effect on digital skills.